Cauchy sequences and a Meir-Keeler type fixed point theorem in partial metric spaces. (JOURNAL OF ADVANCES IN MATHEMATICS, 2016)
In this paper we prove some new conditions for Cauchy sequences by using the diameter of orbit in partial metric spaces. A fixed point theorem for Meir-Keeler type contractions in this space is established.